INTERACTION OF SOCIAL ACTORS IN THE MECHANISM OF COUNTERACTION TO POLITICAL EXTREMISM - Vladis Georgievich Pachalidis (Современная наука и инновации)
The article discusses issues related to the activities of the different social actors performing specific work on counteraction of political extremism.